Augmented reality in Chinese Arts Museums: Enhancing environmental perception and cultural confidence through interactive exhibitions - Wujiu Liu; Noor Azly Mohamed Ali; Bowen Ding; Wahiza Abdul Wahid (Environment and Social Psychology, 2025)
In the era of digital transformation, cultural institutions worldwide are leveraging augmented reality (AR) to redefine visitor experiences, yet the psychological mechanisms underlying AR’s impact on cultural engagement remain underexplored, particularly in the context of Chinese arts museums. This study investigates how AR-mediated interactive exhibitions enhance visitors’ environmental perception (i.e., understanding of artworks’ historical, social, and natural contexts) and foster cultural confidence, integrating theories from environmental psychology and social identity. Using a mixed-methods design, we conducted surveys (N = 500) and semi-structured interviews (n = 30) across three case studies: the Palace Museum’s "Digital Treasure Gallery," Suzhou Museum’s AR Garden, and Hunan Museum’s Mawangdui AR Exhibition. Structural equation modeling (SEM) revealed that AR’s interactivity and immersiveness significantly improved environmental perception (β = 0.62, p < 0.001), which in turn enhanced cultural confidence (β = 0.48, p < 0.01), with a mediating effect accounting for 63% of the total impact. Qualitative analysis identified two key pathways: (1) spatiotemporal reconstruction, where AR recreated artworks’ original environments (e.g., ancient landscapes for traditional Chinese paintings), bridging the gap between historical contexts and modern viewers; (2) emotional resonance, where interactive elements (e.g., virtual craftsmanship simulations) fostered deeper emotional connections to cultural heritage. The findings demonstrate that AR serves as a dynamic tool for translating static art collections into "environmental narratives," enabling visitors to perceive art as embedded in broader ecological and social systems. This dual enhancement of cognitive understanding and emotional identification strengthens cultural self-assurance, aligning with China’s goals of sustainable cultural inheritance (SDG 11.4) and social cohesion (SDG 16.9). For museum practitioners, the study advocates prioritizing "context-rich" AR designs that integrate environmental storytelling over technical spectacle, while highlighting the need for cross-disciplinary collaboration to maximize the psychological impacts of digital cultural initiatives.